2018
DOI: 10.1080/02699052.2018.1493225
|View full text |Cite
|
Sign up to set email alerts
|

Pilot investigation of a novel white matter imaging technique in Veterans with and without history of mild traumatic brain injury

Abstract: Veterans in the post-acute period following mTBI showed limited and spatially heterogeneous MWF changes and myelin integrity was significantly related to processing speed. This preliminary evidence for usefulness of mcDESPOT in combat Veterans with history of mTBI warrants future research to determine mcDESPOT's relative utility compared to techniques such as diffusion tensor imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
6
1
Order By: Relevance
“…In this study, clinical correlations between the myelin volume parameters and various neuropsychological tests were also performed. Unlike the previous study, which reported the association between lower MWF across several ROIs and worse performance on a speeded attention task [ 40 ], we did not find significant correlations between MVF and any of the neuropsychological tests. Furthermore, no correlation was noted between the total myelin volume and neuropsychological test scores, except for the total myelin volume at the bilateral cerebral WM and verbal learning test (delayed recall).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, clinical correlations between the myelin volume parameters and various neuropsychological tests were also performed. Unlike the previous study, which reported the association between lower MWF across several ROIs and worse performance on a speeded attention task [ 40 ], we did not find significant correlations between MVF and any of the neuropsychological tests. Furthermore, no correlation was noted between the total myelin volume and neuropsychological test scores, except for the total myelin volume at the bilateral cerebral WM and verbal learning test (delayed recall).…”
Section: Discussioncontrasting
confidence: 99%
“…Using a 32 echo T2 scan sequence to quantify MWF, Wright et al [ 39 ] demonstrated decreased MWF in several regions of concussed athletes (hockey players), including the corpus callosum, corona radiata, internal capsule, posterior thalamic radiation, and superior longitudinal fasciculus at 2 weeks post-injury as compared to the baseline. In addition, a previous study on veterans with mTBI used multicomponent-driven equilibrium single-pulse observation of T1 and T2 to derive MWF and revealed that MWF was significantly lower in a small number of veterans with a history of mTBI than in those without a history [ 40 ]. In this study, we used an MDME sequence to quantify MVF and showed that the average MVF at the bilateral cerebral WM was lower in mTBI patients with PCS than that in controls, in keeping with those of previous studies [ 39 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pothole analysis has been shown to be sensitive to white matter changes, 88 specifically in mTBI, in previous studies. 31 , 89 , 90 To begin, a normative template based on the MNI-registered DTI volumes of the noTBI participants was generated using tools available within FSL. FSL FAST 91 results were used to restrict the calculations to white matter voxels common among noTBI participants.…”
Section: Methodsmentioning
confidence: 99%
“…Participants included combat-exposed Iraq/Afghanistan veterans primarily recruited from within a Veterans Affairs Medical Center as part of a larger Chronic Effects of Neurotrauma Consortium (CENC) project (Jurick et al, 2018; Merritt et al, 2019). Study procedures included structured interviews assessing combat-related experiences including TBI history and blast exposures as well as current psychiatric diagnoses, administration of self-report questionnaires, and a comprehensive neuropsychological assessment.…”
Section: Methodsmentioning
confidence: 99%